A Novel Approach to Prevent Cache-based Side-Channel Attack in the Cloud. (2016) - Sadique, U.K. Muhammed; James, Divya
Abstract: Cloud computing means different things to different people. It is another way of outsourcing and aggregating any computational hardware service provided over the Internet. It can able to share resources among multiple mutually wariness clients. While there are scads of asset to this system, this sort of resource sharing permit new forms of information leakage across virtual machines. In this paper, we interrogate the time information parameter leakage through cache based side-channel attack and the usage of CPU-cache based side-channels in the cloud. Finally we developed a novel approach which is necessary to mitigate these kinds of attacks in the cloud environment, and correlated to traditional cloud technology.